Did the "After Science and Religion" Project Work in Attempting to Move Scholarly Emphasis from Science and Religion and Towards Metaphysical Theology and Natural Philosophy? - Tyson, Paul (Philosophy, theology and the sciences, 2025)
A distinctive feature of the "After Science and Religion" project was the strong contribution of Ressourcement influenced philosophical theologians. This paper argues that the overarching tenor of project outputs sought to shift the scholarly emphasis from the conceptual landscape of 'science and religion' towards discussions of metaphysical theology and natural philosophy. I argue that this shift in emphasis is genuinely significant and may open up promising new directions in this broad domain of interest. However, there is resistance from existing approaches, which this paper explores. There is resistance to advocating any sort of metaphysical or theological foundation to natural philosophy and natural knowledge. There is resistance to robust conflict about the aims and proper modes of 'science and religion' scholarship which is - I argue - evidence that the Conflict Myth is still powerfully negatively deployed (i. e., we must never allow conflict). The paper explores both of these sites of resistance via the unease John Perry and Joanna Leidenhag, advocating Science Engaged Theology, have towards John Milbank's metaphysical theology approach to natural philosophy and the natural sciences. My paper finds in favour of Milbank over Perry/Leidenhag and proposes that the "After Science and Religion" project has been a modest and promising success.